THE IMPACT OF IMMUNE STATUS CHARACTERISTICS ON THE RESULTS OF IN VITRO FERTILIZATION IN PATIENTS WITH INFERTILITY - Ismayilova, M.K. (World of Medicine and Biology, 2023)
The purpose of our study was to assess the levels of immunological indicators in infertile patients with positive and negative results of in vitro fertilization procedure. The study of indicators of immune status was conducted in 54 married couples. The concentration of immunoglobulins A, M and G were tested by the radial immunodiffusion method. The main lymphocyte populations–T-lymphocytes, T-helpers, cytolytic T-cells, natural killers, B-lymphocytes against monoclonal antibodies, respectively, CD3, CD4, CD8, CD16, CD19, CD25, HLA-DR, CD4/CD8 were studied. Indicators of immune imbalance in both partners were found in 7 % of married couples (in men were determined in 9 % of cases, in women–in 15 % of cases). In infertile women the number of T-helpers significantly exceeds the indicators of men in both the main and control groups (р